2019
DOI: 10.1021/acs.chemrestox.8b00369
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole–Hemoglobin Adducts, a More Feasible Potential Biomarker of Pyrrolizidine Alkaloid Exposure

Abstract: Pyrrolizidine alkaloids (PAs) are naturally occurring phytotoxins widely distributed in about 3% of flowering plants. The formation of PA-derived pyrrole–protein adducts is considered as a primary trigger initiating PA-induced hepatotoxicity. The present study aims to (i) further validate our previous established derivatization method using acidified ethanolic AgNO3 for the analysis of pyrrole–protein adducts and (ii) apply this method to characterize the binding tendency, dose–response, and elimination kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…Since then, over 15,000 acute PA-poisoning cases with obvious clinical symptoms have been documented worldwide in many regions/countries, including Afghanistan, China, Germany, Hong Kong, India, Jamaica, South Africa, Switzerland, the United States, etc. (Lin et al 2011 ; Ma et al 2019 ; Ruan et al 2015 ; Zhu et al 2020 ). Nevertheless, the diagnosis of the majority of these reported poisoning cases was based on typical symptoms of HSOS with either known history of exposure to PA-producing herbs or PA-contaminated foodstuffs or through retrospective investigations to confirm the PA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, over 15,000 acute PA-poisoning cases with obvious clinical symptoms have been documented worldwide in many regions/countries, including Afghanistan, China, Germany, Hong Kong, India, Jamaica, South Africa, Switzerland, the United States, etc. (Lin et al 2011 ; Ma et al 2019 ; Ruan et al 2015 ; Zhu et al 2020 ). Nevertheless, the diagnosis of the majority of these reported poisoning cases was based on typical symptoms of HSOS with either known history of exposure to PA-producing herbs or PA-contaminated foodstuffs or through retrospective investigations to confirm the PA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Further study identified pyrrole-lysine adducts in PA-treated mice, which supported the formation of PPAs in vivo (Li et al 2016). Other proteinogenic amino acids, such as cysteine, valine, and histidine were further found to be capable of binding to the pyrrole moiety through chemical synthesis in the in vitro or in vivo models (Estep et al 1990;He et al 2016aHe et al , b, 2017Ma et al 2019;Xia et al 2015;Zhao et al 2014). All these results support that both DHPAs and DHP possessing bi-functional electrophilic substituents at C7 and C9 positions of the core pyrrole moiety are capable of alkylating to the nucleophilic sites at the -SH and -NH functional groups of the target proteins, leading to the formation of PPAs (Fig.…”
Section: Formation Of Pyrrole-protein Adductsmentioning
confidence: 84%
“…DHPAs can rapidly eject a carboxylate leaving group from C1-acyloxymethyl or C7-acyloxy substituents and form intermediates with carbocation. Such iminium intermediates are highly reactive with half-lives of a few seconds in water (Mattocks and Jukes 1990) and capable of alkylating cellular constituents such as proteins and DNA (Ma et al 2019;Xia et al 2013). DHPAs can be further hydrolyzed to ( ±)-6,7-dihydro-7-hydroxy-1-hydroxymethyl-5H-pyrrolizine (DHP), which is more water-soluble and less reactive compared with DHPAs but still displays a moderate level of alkylating activity; hence both DHPAs and DHP are considered as reactive metabolites of PAs (Mattocks 1986;Robertson 1982).…”
Section: Metabolism Of Retronecine-type and Heliotridine-type Pasmentioning
confidence: 99%
See 2 more Smart Citations